Pengembangan Bakat Siswa melalui Kegiatan Belajar Kaligrafi dalam Meningkatkan Motivasi Belajar PAI di Pondok Pesantren Raudhatul Jannah Kota Subulussalam - Zeki Zulkarnain; Warul Walidin; T. Lembong Misbah (Tadabbur: Jurnal Peradaban Islam, 2023)
The development of student talents is more often found in Islamic boarding schools because Islamic boarding schools have a function other than as a religious education institution as well as a place to develop student's talents and potential holistically. One of the extracurricular activities that students are interested in is calligraphy extracurricular. This study aims to analyze the development of students' talents through calligraphy learning activities in increasing motivation to study PAI at the Raudhatul Jannah Islamic Boarding School. The research method used is qualitative research with a case study approach. Data collection techniques used are interviews, observation, and documentation. The data obtained were analyzed using qualitative data analysis methods using data reduction, data presentation, and conclusion. The results of the study show that calligraphy extracurricular activities can develop students' talent in calligraphy and at the same time can also increase motivation to learn PAI. Learning calligraphy at Islamic boarding schools is carried out in a structured and organized way, starting from preparation, and teaching, to evaluation. Students who participate in calligraphy extracurricular activities get benefits such as developing skills, increasing creativity, and increasing motivation to learn PAI. However, there are still obstacles such as the lack of support from parents, the lack of adequate equipment, and the lack of time available for extracurricular activities. In order to improve the development of students' talents through calligraphy learning activities at the Raudhatul Jannah Islamic boarding school, researchers provide suggestions such as increasing the role of parents, increasing adequate equipment, and increasing the time available for calligraphy extracurricular activities.